Can CBT Be Effective for Aboriginal Australians? Perspectives of Aboriginal Practitioners Trained in CBT. (February 2014) - Bennett‐Levy, James; Wilson, Shawn; Nelson, Jeff; Stirling, Janelle; Ryan, Kelleigh; Rotumah, Darlene; Budden, Wayne; Beale, Dean
<x xml:space="preserve">Abstract</x> The objective of the study was to investigate whether high and low intensity versions of cognitive behaviour therapy (CBT) might be an effective therapeutic approach for enhancing the mental health of Aboriginal Australians. Five university‐educated Aboriginal counsellors received in‐depth training in CBT. Over the following year, they used CBT strategies with their clients, and met 10 times as a participatory action research group. The group addressed three key questions: (a) Does CBT appear to be useful for Aboriginal Australians? (b) If so, what elements of CBT are perceived to be effective? (c) What adaptations might be made to CBT to enhance its effectiveness with Aboriginal Australians? The resulting qualitative data were transcribed and analysed. Counsellors perceived CBT to be very useful for their Aboriginal clients and for themselves. They reported that it enhanced their clients' well‐being, their own clinical skills, and their own well‐being, and it reduced burnout. The qualities of CBT that were perceived to be effective were its adaptability, pragmatic here‐and‐now approach, capacity for low‐intensity interventions, safe containing structure, promotion of self‐agency, and valuable techniques. It was suggested that the prime requirement for adaptations to CBT were that they would need to fit different social and cultural contexts.